Teaching Material using SETS Approach for Volcanic Dust Disaster Mitigation - Cherly Salawane; Supriyadi Supriyadi; Ani Rusilowati; Dyah Rini Indriyanti; Achmad Binadja (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2020)
Mitigation education is a stage of preparedness to minimize losses due to a disaster. The purpose of this study is to develop teaching materials with the SETS (Science, Environment, Technology, and Society) approach Integrated Science subjects of solar system competencies and the earth surface structure to reduce the risk of the Mount Lokon volcanic ash disaster in North Sulawesi Province. This research uses Research and Development Methods. The subjects in this study were 30 students at SMP Kristen Credo Kolongan, Minahasa Regency. The results showed that the teaching material developed was declared valid by experts, practical was used, and effectively viewed from the cognitive aspect with an increase in the pretest score (54.5) to the posttest (92), and the affective aspects of the average score very good average (87.3) so that this teaching material is valid, practical, and effectively used in learning activities to reduce the risk of volcanic ash disaster.